2002
DOI: 10.1111/j.1572-0241.2002.05424.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscope length and procedure efficiency

Abstract: Although the length of the intermediate instrument rarely compromises colonoscopy, it offers no significant advantage over the long scope for routine procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Controversy exists concerning the benefits of ILAC in CIT. Dickey and Garrett (18) reported that there were no differences in the CIR and CIT with respect to the length of colonoscope used. However, although the difference was not statistically significant, there was a trend toward a shorter CIT in the ILAC group (ILAC group, 7.73 min vs LLAC group, 8.11 min; P = 0.44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Controversy exists concerning the benefits of ILAC in CIT. Dickey and Garrett (18) reported that there were no differences in the CIR and CIT with respect to the length of colonoscope used. However, although the difference was not statistically significant, there was a trend toward a shorter CIT in the ILAC group (ILAC group, 7.73 min vs LLAC group, 8.11 min; P = 0.44).…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, most colonoscopists may recognize that colonoscope length may influence the completion rate of intubation of the terminal ileum. Although there have been no studies directly investigating the association between the length of colonoscope and terminal ileal intubation, previous studies have found plenty of evidence that long scopes offer the highest chance of successful cecal intubation (17, 18, 21, 22, 26). In this study, the longer scope also appeared to offer a higher success rate for terminal ileal intubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous studies 9, 10 have evaluated the length of colonoscope on procedure efficiency. Barthel No one colonoscope is ideal for all patients, and different subgroups of patients may require different colonoscopes.…”
Section: Discussionmentioning
confidence: 99%
“…9 In contrast, Dickey found that there was no difference in completion rates or cecal intubation times when comparing scopes of two different lengths. 10 A long pediatric colonoscope is longer and thinner than an intermediate length adult colonoscope. We hypothesized the pediatric colonoscope might be less efficient because of these two features.…”
Section: Introductionmentioning
confidence: 99%